2015
DOI: 10.3389/fnmol.2015.00068
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress Effects on Glucocorticoid—BDNF Interplay in the Hippocampus

Abstract: Early life stress (ELS) is implicated in the etiology of multiple psychiatric disorders. Important biological effects of ELS are manifested in stress-susceptible regions of the hippocampus and are partially mediated by long-term effects on glucocorticoid (GC) and/or neurotrophin signaling pathways. GC-signaling mediates the regulation of stress response to maintain homeostasis, while neurotrophin signaling plays a key role in neuronal outgrowth and is crucial for axonal guidance and synaptic integrity. The neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 102 publications
(82 reference statements)
2
75
1
2
Order By: Relevance
“…Hippocampal inhibitory control of HPA axis activity, which is a normal phenomenon in homeostasis, is also known to be compromised in chronic restraint stress (115,121); and along with glucocorticoids, NGFs are known to be central players causing this dysregulation (109,112,122). Hippocampal pyramidal neurons secrete NGFs in response to stress which correspond to HPA axis activity (123,124), and also TrkB, the receptor for BDNF is found to be co-localized with glucocorticoid receptor (GR) and having mutual influence on each other's signalling in these neurons (122).…”
Section: Fig 2 Stress Induced Hpa Axis Mediated Disruption In Ngfs mentioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal inhibitory control of HPA axis activity, which is a normal phenomenon in homeostasis, is also known to be compromised in chronic restraint stress (115,121); and along with glucocorticoids, NGFs are known to be central players causing this dysregulation (109,112,122). Hippocampal pyramidal neurons secrete NGFs in response to stress which correspond to HPA axis activity (123,124), and also TrkB, the receptor for BDNF is found to be co-localized with glucocorticoid receptor (GR) and having mutual influence on each other's signalling in these neurons (122).…”
Section: Fig 2 Stress Induced Hpa Axis Mediated Disruption In Ngfs mentioning
confidence: 99%
“…Hippocampal pyramidal neurons secrete NGFs in response to stress which correspond to HPA axis activity (123,124), and also TrkB, the receptor for BDNF is found to be co-localized with glucocorticoid receptor (GR) and having mutual influence on each other's signalling in these neurons (122). A study by Lambert et al has shown in primary rat cortical neurons that BDNF induces structural change at GR gene (phosphorylation at serine 155 and 287) and causes significant change in its transcriptome (125).…”
Section: Fig 2 Stress Induced Hpa Axis Mediated Disruption In Ngfs mentioning
confidence: 99%
“…Convergence of research results across rodents and humans has been reviewed elsewhere and I highlight a few reviews, although many other excellent reviews are available (Branchi & Cirulli, 2014;CadizMoretti, Otero-Garcia, Martinez-Garcia, & Lanuza, 2014;Callaghan & Tottenham, 2016;Chen & Baram, 2016;Daskalakis, De Kloet, Yehuda, Malaspina, & Kranz, 2015;Davis & Pfaff, 2014;Gee & Casey, 2015;Molet, Maras, Avishai-Eliner, & Baram, 2014;Patchev, Rodrigues, Sousa, Spengler, & Almeida, 2014;Rincon-Cortes & Sullivan, 2014;Tang, ReebSutherland, Romeo, & McEwen, 2014;Tost, Champagne, & Meyer-Lindenberg, 2015;Turecki & Meaney, 2016).…”
Section: Historical Insights: the Importance Of Animal Research To Atmentioning
confidence: 99%
“…Hippocampal inhibitory control of HPA axis activity, which is a normal phenomenon in homeostasis, is also known to be compromised in chronic restraint stress (116,122); and along with glucocorticoids, NGFs are known to be central players causing this dysregulation (109,112,123). Hippocampal pyramidal neurons secrete NGFs in response to stress which correspond to HPA axis activity (124,125), and also TrkB, the receptor for BDNF is found to be co-localized with glucocorticoid receptor (GR) and having mutual influence on each other's signalling in these neurons (123).…”
Section: Fig 2 Stress Induced Hpa Axis Mediated Disruption In Ngfs mentioning
confidence: 99%